Stability of 25 mg/mL Azacitidine Suspensions Kept in Fridge after Freezing - Balouzet Clara; Chanat Cédric; Jobard Marion; Brandely-Piat; Chast François (De Gruyter, 2017)
Azacitidine is supplied as lyophilized powder to be reconstituted with sterile water for injection. The molecule is very unstable in aqueous medium (temperature-dependent process). Advance preparation and leftover management are made difficult by such poor stability. This study evaluates the stability of 25 mg/mL azacitidine suspensions kept for a 1-month period at -20 °C, followed by a 5-day period at 5 °C. Three batches of 7 polypropylene syringes were filled with 2 mL of Vidaza® (Celgene, France) reconstituted with cold sterile water for injection: 1 syringe was immediately analysed, the other 6 were stored at -20 °C. After 1 month, the 6 syringes were defrosted at room temperature (20 min) and then stored in a refrigerator at 2-8 °C. Experimental timings were determined as follows: preparation day (Dfab), defrosting day (D0) and every 24 h for the following 5 days (from D1 to D5). Several types of analyses were carried out: visual inspections, microscopic observations of crystal shape, turbidity measurements (UV-visible spectrophotometry) and UV-HPLC analyses (stability assessment method adapted from Harting et al). The ICH Guidelines' specifications of 5 % change were retained. At D0, after 1 month at -20 °C, the volume contained in the syringes showed an increase (+5 %), and a phase separation, reversible by strong agitation, was observed. From the microscopic point of view, crystals appeared to be larger at D5 than at D0. With regard to content, average losses of 4.5 % at D3 and 8.3 % at D5 were observed. Freezing efficiently prevents azacitidine from degrading. Advance preparation of 25 mg/mL azacitidine syringes can therefore be achieved provided they are immediately frozen at -20 °C and then stored at 5 °C for 3 days.